CD36 attenuates pressure overload-induced myocardial insulin resistance via HSF1-dependent HSP90α suppression and competitive disruption of the HSP90α-InsR complex - Hongyang Shu; Na Li; Qinqing Zhao; Zixuan Zhang; Yating Qin; Jiali Nie; Dao Wen Wang; Ning Zhou (Journal of Translational Medicine)
Abstract Background Insulin resistance (IR) is an early hallmark of pressure overload-induced myocardial injury and heart failure. Although CD36, a fatty acid transporter, regulates systemic insulin sensitivity, its role in myocardial insulin resistance under pressure overload remains unclear. This study aimed to elucidate CD36’s cardioprotective mechanisms in this context. Methods Myocardial tissues from dilated cardiomyopathy patients, transverse aortic constriction (TAC) mice, and cultured hypertrophic cardiomyocytes were analyzed for CD36 expression and insulin sensitivity. CD36 overexpression was induced via rAAV9-tnt-CD36. InsR-interacting proteins in CD36-overexpressing cells were profiled using tandem mass spectrometry, identifying HSP90α as the key partner. HSP90α agonists were used in rescue experiments. Glucose uptake (2-NBDG assay) and InsR/Akt phosphorylation were measured. Mechanistic studies included immunofluorescence, subcellular fractionation, and HSF1 transcriptional regulation analysis. Results CD36 levels and insulin sensitivity were reduced in dilated cardiomyopathy patients, TAC mice, and hypertrophic cardiomyocytes. CD36 overexpression enhanced glucose uptake and insulin signaling. Mass spectrometry identified HSP90α (not HSP90β) as the critical InsR partner modulated by CD36. HSP90α agonists reversed CD36-mediated improvements in glucose uptake and InsR/Akt phosphorylation. Mechanistically, CD36 disrupted HSP90α-InsR binding via (1) HSF1-dependent transcriptional suppression of HSP90α and (2) competitive displacement of HSP90α from InsR. Pathological conditions increased cytosolic InsR-HSP90α trapping, while CD36 redistributed InsR to the plasma membrane. Conclusion CD36 mitigates pressure overload-induced insulin resistance by dual mechanisms: suppressing HSP90α expression via HSF1 inhibition and competitively displacing HSP90α to promote InsR membrane localization. This stabilizes insulin signaling and restores metabolic homeostasis, highlighting CD36 as a therapeutic target for heart failure involving metabolic-cardiac crosstalk.